2013
DOI: 10.1016/j.actatropica.2013.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in clinical signs and cellular immunity of dogs with visceral leishmaniasis using the immunomodulator P-MAPA

Abstract: This study investigated the immunotherapeutic potential of the protein aggregate magnesium-ammonium phospholinoleate-palmitoleate anhydride immuno-modulator (P-MAPA) on canine visceral leishmaniasis. Twenty mongrel dogs presenting clinical symptoms compatible with leishmaniasis and diagnosis confirmed by the detection of anti-leishmania antibodies were studied. Ten dogs received 15 doses of the immunomodulator (2.0 mg/kg) intramuscularly, and 10 received saline as a placebo. Skin and peripheral blood samples w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 39 publications
0
17
0
7
Order By: Relevance
“…The most common drugs used for CanL are the meglumine antimoniate, miltefosine and allopurinol. However, in recent years attempts have been made to use immumodulatory molecules for treatment of CanL such as the protein aggregate magnesium-ammonium phospholinoleate-palmitoleate anhydride immumo-modulator (P-MAPA) (Santiago et al 2013) that appears to induce TLR2 in human embryonic kidney (HEK) cells (Favaro et al 2012) and in canine macrophages (Melo et al 2014 b ). The treatment with this immumodulator resulted in an improvement in clinical signs and a significant reduction in parasite load in the skin.…”
Section: Treatment Of Clinical Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…The most common drugs used for CanL are the meglumine antimoniate, miltefosine and allopurinol. However, in recent years attempts have been made to use immumodulatory molecules for treatment of CanL such as the protein aggregate magnesium-ammonium phospholinoleate-palmitoleate anhydride immumo-modulator (P-MAPA) (Santiago et al 2013) that appears to induce TLR2 in human embryonic kidney (HEK) cells (Favaro et al 2012) and in canine macrophages (Melo et al 2014 b ). The treatment with this immumodulator resulted in an improvement in clinical signs and a significant reduction in parasite load in the skin.…”
Section: Treatment Of Clinical Diseasementioning
confidence: 99%
“…The treatment with this immumodulator resulted in an improvement in clinical signs and a significant reduction in parasite load in the skin. Peripheral blood mononuclear cells (PBMC) cultures also showed an increase in IL-2 and IFN- γ and a decrease in IL-10 levels (Santiago et al 2013). Taken together, the findings from this study indicated that P-MAPA has the potential to be used as an immunotherapeutic drug in CanL (Santiago et al 2013).…”
Section: Treatment Of Clinical Diseasementioning
confidence: 99%
“…Using an immunomodulator, Santiago et al (126) tested the immunotherapeutic effect for CVL of a protein aggregate of magnesium–ammonium phospholinoleate–palmitoleate anhydride (P-MAPA) obtained by fermenting the fungus Aspergillus oryzae . P-MAPA showed immunomodulatory activity, with greater stimulation of cellular immunity and no toxic effects in mice and dogs (127).…”
Section: Progress For Vl Treatment In Dogsmentioning
confidence: 99%
“…To investigate the immunotherapeutic potential of P-MAPA, symptomatic dogs were submitted to a protocol of 15 doses of the immunomodulator (2.0 mg/kg) intramuscularly. An increase in CD8 + T cells in peripheral blood, a decrease in IL-10 levels, and an increase in IL-2 and IFN-γ, improved clinical signs, and reduced skin parasitism were obtained after immunotherapy (126). …”
Section: Progress For Vl Treatment In Dogsmentioning
confidence: 99%
“…These observations suggested that P-MAPA has potential as an immunotherapeutic drug in canine visceral leishmaniasis, but not in vitro, since it assists in reestablishing partial immunocompetence of infected dogs. 97 Several parameters in healthy and Leishmania-infected dogs treated with P-MAPA were studied. Macrophages in culture of peripheral blood mononuclear cell (PBMC) were isolated.…”
Section: Phosphate Accumulation In Organismsmentioning
confidence: 99%